A Critical Study of Kant’s Approach to Freedom from the Islamic Philosophy Perspective - Ali Ansari Baygi; Ali Jalaeian Akbarnia; Davoud Heidari (آموزه‌‌های فلسفه اسلامي)
Freedom is one of the issues that have been considered in different divine and human schools including the moral and legal system of Kant’s philosophy as well as the teachings and doctrines of Islamic philosophy. Since the influence of Kant’s ideas on the question of freedom on the practical science (ethics) prevailing in the era of modernity is undeniable and paying attention to his views in this discussion can provide a better understanding of modern practical philosophy and its relation to the thoughts of Muslim philosophers. Therefore, the main problem of this paper is the critical study of Kant’s attitude to the issue of freedom and intellectual aspects in relation to the Islamic philosophy fundamentals is the main issue of this article. This study analyzes Kant’s view in this field and his fundamentals by a critical analytical method and then with a comparative approach examines the relation between the views of Muslim philosophers with him. The findings of this study suggest that the critical approach of Islamic philosophy to Kant is from two aspects; first: epistemological methodology in the discussion of the compatibility of free rationality and religion; second, in terms of the role of freedom in the legal system and conflict in its value position. Therefore, this research can be considered innovative in terms of philosophical approach to the problem and Kant’s view from the perspective of Islamic ethics.